Hybrid lead halide [(CH3)2NH2]PbX3 (X = Cl− and Br−) hexagonal perovskites with multiple functional properties. Issue 32 (1st August 2019) - García-Fernández, Alberto; Juarez-Perez, Emilio Jose; Bermúdez-García, Juan Manuel; Llamas-Saiz, Antonio Luis; Artiaga, Ramón; López-Beceiro, Jorge Jose; Señarís-Rodríguez, María Antonia; Sánchez-Andújar, Manuel; Castro-García, Socorro
Abstract : [(CH3 )2 NH2 ]PbX3 (X = Cl − and Br − ) hexagonal perovskites exhibit a first order phase transition, dielectric transition and broad red light photoluminescence emission. Abstract : We have been able to prepare two new lead halides with the formula DMAPbX3 (where DMA is dimethylammonium and X is Cl − or Br − ), which display a 4H-hexagonal perovskite polytype, an unusual crystal structure in hybrid organic–inorganic perovskites. Both compounds experience a first-order phase transition, the chloride at ∼320 K and the bromide at ∼250 K, which involves two cooperative processes: an off-center shift of the lead cations and an order–disorder process of the DMA cations. Additionally, a sharp dielectric transition is associated with this structural transition in both hybrids. Both compounds are semiconductors with band gap values of 3.5 eV (X: Cl − ) and 3.0 eV (X: Br − ). Also, the LT-phase of the Br − compound displays a broad red light photoluminescence (PL) emission (620 nm) and PLE excitation with the maximum at a soft UV wavelength (360 nm). This broadband emission and large Stokes-shifted PL seem to be related to a self-trapped exciton mechanism. Therefore, the uncommon 4H-hexagonal perovskite is a promising crystal structure for understanding and designing new hybrid materials with broad photoluminescent emission and dielectric properties.